Fungal sex for disease control and strain improvement - Pearson, Thomas (2021)
The overarching theme of this thesis was to explore if and how sexual reproduction in fungi could be exploited for disease control and strain improvement. Work focussed on two distantly related members of the Pezizomycotina; Pyrenopeziza brassicae, an important pathogen of Brassica napus (oilseed rape) and other Brassica species; and Penicillium roqueforti, the famous species used for commercial production of blue cheeses.